Autonomy of Religious Organizations in the Legal Order of the Republic of Serbia - Đukić, Dalibor B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The right of religious organizations to independently decide on purely religious issues is one of the basic prerequisites is fundamental for upholding both communal and individual aspects of religiousfreedom. The scope and content of religious autonomy may differ depending on the model of the relationship between the state and churches and religious communities. The basic hypothesis of the paper is that the protection of religious autonomy in Serbia does not deviate from the general international standards established by international conventions for the protection of human rights and the jurisprudence of the European Court of Human Rights. However, there remains an opportunity for enhancement, particularly concerning the protection of rights for various factions resulting from divisions within formerly unified religious entities.